The Role Of Verbal And Non-Verbal Means Of Communication And Their Application In Social Networks - Rahmonova Aziza Ruzikul kizi (Academia One Publishing, 2024)
The article considers the historical aspect emergence of iconographic signs as a means expressions of semantic and connotative meaning when transmitting information, they were compared with modern means of non-verbal communication. Based on analysis nonverbal means of communication and their application in social networks of the Internet in the article rises the problem of systematization and scientific approach to use of non-verbal means to simplify use. As a result of an increase in the number of characters, there are difficulties in choosing and correctly assessing its connotative meaning
Keywords: non-verbal; communication; emoticons; emoji